Charging Effects and Detection of Mesospheric Dust with the Instrument SPID on the G-Chaser Rocket - Gunnarsdottir, Tinna (UiT Norges arktiske universitet, 2019)
Smoke Particle Impact Detector (SPID) is a faraday cup impact probe designed and built by the University of Tromso (UIT). Its main purpose is to measure nanometer sized smoke particles (in-situ) in the atmosphere, and to do that it needs to be launched on a sounding rocket. Its design is an open faraday cup with grids to shield out ambient plasma and a larger slanted impact grid to measure the incoming smoke. The particles we are interested in measuring are called Meteoric Smoke Particles (MSPs). They are believed to be condensed material from meteoric ablation and thought to reside in layers in the altitude range of approximately 50-100 km with sizes of around 0.2-3 nm on average. There are many unknowns regarding the smoke particles, particularly their altitude distribution, size, charge and composition. By gaining more knowledge about them we can start to understand better their involvement in atmospheric processes including their possible impact on chemical reactions and formation of ice particles in the mesosphere and the possible connection to Polar Mesospheric Winter Echoes(PMWE). SPID was launched for the first time on the student rocket G-Chaser in January 2019. The launch was successful apart from some minor issues regarding amplification on the shielding grids. The main grid designed to measure the smoke showed a positive current during the entire flight with some interesting areas that might indicate detection of smoke particles. This thesis focuses on estimating the charging of the payload by ambient plasma and induced photocurrent from UV solar photons, as well as the possibility of solar induced currents on the grids and their possible contribution to the measured currents. We find that the payload is primarily negatively charged with an estimated floating potential of maximum 0.46 V up towards apogee of around 184 km with charging due to ambient electrons dominating the examined charging sources. Calculations also determined that there it is possible for the induced photocurrent on the grids to ...